2021
DOI: 10.1177/1757913921992405
|View full text |Cite
|
Sign up to set email alerts
|

Is children’s health-related quality of life associated with physical fitness and mode of commuting? PREVIENE Project

Abstract: Aim: The aims of this study were (1) to examine the associations between self-reported health-related quality of life (HRQoL), health-related physical fitness (cardiorespiratory fitness, muscular strength, and speed-agility), and mode of commuting to and from school in Spanish children, and separately by gender and (2) to analyse the difference in cardiorespiratory fitness by mode of commuting to and from school by gender. Methods: We conducted a cross-sectional analysis that included 415 children aged 8.47 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 39 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…Our cross-sectional results showed a positive association between CRF and HRQoL. Similar findings were found in previous studies, [11][12][13]39 which reported that children with higher levels of CRF had better HRQoL. For instance, a study in Norwegian 10-year-olds revealed that CRF had a small to medium effect size (R 2 ranging from 0.17 to 0.5) in its positive association with all HRQoL domains (i.e., physical and psychological well-being, autonomy and parents, social support and school environment).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our cross-sectional results showed a positive association between CRF and HRQoL. Similar findings were found in previous studies, [11][12][13]39 which reported that children with higher levels of CRF had better HRQoL. For instance, a study in Norwegian 10-year-olds revealed that CRF had a small to medium effect size (R 2 ranging from 0.17 to 0.5) in its positive association with all HRQoL domains (i.e., physical and psychological well-being, autonomy and parents, social support and school environment).…”
Section: Discussionsupporting
confidence: 92%
“…10 Previous research suggests that CRF may be a potentially useful strategy to enhance children's HRQoL, however evidence of this relationship is limited to cross-sectional studies. [11][12][13] For example, Andersen et al's study of 1129 schoolchildren aged 10 years, showed that CRF was positively associated with overall HRQoL. 11 Another study including 415 children aged between 8 and 9 years reported a positive weak correlation between CRF and HRQoL in boys, but not in girls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity has emerged as a useful tool to maintain a healthy lifestyle [ 17 ]. In this regard, several studies have pointed out the relationship between physical activity and HRQoL [ 18 , 19 , 20 , 21 , 22 ]. Thus, more than sixteen articles in the last year and a half have explored this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a previous study showed that physical activity levels can predict HRQoL in children as well as that physical activity is the main behavior in the prediction of the quality of life for a population of school adolescents [ 20 ]. Furthermore, improvements in cardiorespiratory fitness may be useful to improve HRQoL [ 18 , 19 ]. Strengthening the relationship between level of physical activity and HRQoL, we can find different articles exploring sedentary behaviors and their relation to HRQoL [ 21 ].…”
Section: Introductionmentioning
confidence: 99%